2006
DOI: 10.1115/1.2202152
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Optical Performance of the Space Interferometry Mission Using a Modeling, Testing, and Validation Methodology

Abstract: This paper presents the modeling, testing, and validation methodologies developed to predict the optical performance of the Space Interferometry Mission (SIM) at the Jet Propulsion Laboratory (JPL). The modeling methodology combines structural, optical, and control system design within a common state space framework and incorporates reaction wheel assembly (RWA) disturbances to evaluate the end-to-end performance of the system requirements. The validation methodology uses the Micro-Precision Interferometer (MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 7 publications
0
23
0
Order By: Relevance
“…Earlier works on RWAs have shown that the diagonal coecients (D wii with i = 1, 2, 3, 4, 5, 6) are generally the most important ones [29,32]. Moreover, the four cross-DoF terms D w15 , D w24 , D w42 , and D w51 have also to be considered, in particular for non-symmetric congurations (i.e.…”
Section: Dynamic Massmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier works on RWAs have shown that the diagonal coecients (D wii with i = 1, 2, 3, 4, 5, 6) are generally the most important ones [29,32]. Moreover, the four cross-DoF terms D w15 , D w24 , D w42 , and D w51 have also to be considered, in particular for non-symmetric congurations (i.e.…”
Section: Dynamic Massmentioning
confidence: 99%
“…Its parameters will, in fact, not only change as a function of the frequency but also of the speed of the rotary ywheel. In [29,32], analytical expressions of RWA dynamic mass including the gyroscopic eect based on a RWA hard-mounted microvibration model were derived and used for coupled microvibration analysis. Although the results were improved, the modes of vibration of the RWA were not included hence limiting the quality of predictions.…”
mentioning
confidence: 99%
“…(22), and expressing explicitly the moment produced by the rotation of the point mass m e (see Fig. 6), the following alternative form of the equations is obtained: (25) where r is the radius of the flywheel. Equation (25) is then used to calculate numerically !…”
Section: Acceleration Verificationmentioning
confidence: 99%
“…However, in [23] the development of the mathematical model of the RWA (cantilevered flywheel with rigid bearing in this case) is not included, and input disturbance data are empirical (from RWA vibration tests). This method was then applied to assess the optical performance of the Space Interferometry Mission in [24,25].…”
Section: Doi: 102514/1j050791mentioning
confidence: 99%
“…However, this method is not an accurate representation of the coupled boundary conditions that occur when the PTC is mounted to a structure. With the aim to analytically reproduce the coupled dynamics, a dynamic mass method was developed to evaluate the coupled performance [11][12][13]. Although the results are accurate, this method is significantly challenging in terms of test configuration and computational effort.…”
Section: Introductionmentioning
confidence: 99%